Isolated Marked Inferior Vena Cava Dilatation: Unusual Presentation or Underrecognized Common Phenomenon? - Sneha R. Gadi; Benjamin K. Ruth; Alan Johnson; Sula Mazimba; Younghoon Kwon (Case Reports in Cardiology)
Inferior vena cava (IVC) diameter and respirophasic variation are commonly used echocardiographic indices to estimate right atrial pressure. While dilatation of the IVC and reduced collapsibility have traditionally been associated with elevated right heart filling pressures, the significance of isolated IVC dilatation in the absence of raised filling pressures remains poorly understood. We present a case of an asymptomatic 28-year-old male incidentally found to have IVC dilatation, reduced inspiratory collapse, and normal right heart pressures.